McCarthyism and the Mathematization of Economics - E. Roy Weintraub (Duke University, Center for the History of Political Economy (CHOPE), 2016)
Historians of the social sciences and historians of economics have come to agree that, in the United States, the 1940s transformation of economics from political economy to economic science was associated with economists' engagements with other disciplines—e.g. mathematics, statistics, operations research, physics, engineering, cybernetics—during and immediately after World War II. More controversially, some historians have also argued that the transformation was accelerated by economists' desires to be safe, to seek the protective coloration of mathematics and statistics, during the McCarthy period. This paper argues that that particular claim 1) is generally accepted, but 2) is unsupported by good evidence, and 3) what evidence there is suggests that the claim is false.
Keywords: B2; B4; B5; C02; C10; 330; Cold War; McCarthyism; mathematical economics; mathematization of economics; history of philosophy; RAND; Cowles Commission; Paul Lazarsfeld